Single-Chain Polymer Nanoparticles : Synthesis, Characterization, and Applications. - Pomposo, José A. (John Wiley & Sons, Incorporated, 2017)
This first book on this important and emerging topic presents an overview of the very latest results obtained in single-chain polymer nanoparticles obtained by folding synthetic single polymer chains, painting a complete picture from synthesis via characterization to everyday applications. The initial chapters describe the synthetics methods as well as the molecular simulation of these nanoparticles, while subsequent chapters discuss the analytical techniques that are applied to characterize them, including size and structural characterization as well as scattering techniques. The final chapters are then devoted to the practical applications in nanomedicine, sensing, catalysis and several other uses, concluding with a look at the future for such nanoparticles. Essential reading for polymer and materials scientists, materials engineers, biochemists as well as environmental chemists.